(untitled) (American Journal of Islam and Society, 2023)
The Qurʾan is the primary source of inspiration for Muslims across the ages. As Muslims, the task is to make the Qurʾan relevant to our own context. That task is however challenged every time the conception of the world changes. The change from a medieval Aristotelian to a modern heliocentric view of the world represented just such a challenge. But regardless of the differing worldviews, the Qurʾan’s descriptions of natural phenomena remained relevant. Accordingly, the aim of this article is to demonstrate the correspondence between the Qurʾanic description of natural phenomena and various scientific paradigms. It claims that the Qurʾan is relevant to both past and present scientific paradigms, even if these paradigms conflict with one another. This claim is illustrated through the example of cosmographies. It shows that the Qurʾan’s cosmographical verses can be read considering both ancient and modern paradigms. This multiplicity of correspondences is achieved: (1) by means of subjective descriptions, which are open to interpretation, (2) by means of negative affirmations, which allude to certain paradigms without fully endorsing them, and (3) through a silence about key elements that would unambiguously validate or refute a specific scientific paradigm. The Qurʾan’s interpretatively open cosmographical verses also include particularly apt word choices and morphology when it comes to considering them in the light of modern scientific paradigms. The philosophical and theological consequences of this multiplicity of correspondence are also discussed.